The Influence of Cafe Atmosphere, Wom, and Customer Experience on Repeat Purchases of Coffee at Coffee Shops in an Islamic Business Perspective (Study on Generation Z Visitors to Hero Coffee Shop In Bandar Lampung City) - Putri, Hamisah Ramadhania; Fasa, Muhammad Iqbal; Fachri, Adib (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine and analyze the effect of Cafe Atmosphere, Word Of Mouth and Customer Experience on Repeat Purchase of Coffee at Coffeshop in Islamic Business Perspective. This study uses Purposive Sampling technique, using Nonprobability Sampling method with a sample size of 96 respondents using the Lemeshow formula. The data analysis method using SEM PLS analysis is processed with the SmartPLS 4.0 application. The results of the analysis show that partially the Word Of Mouth and Customer Experience variables affect Repeat Purchase, while the Cafe Atmosphere variable has no effect on Repeat Purchase.